Grain growth behavior in bismuth titanate-based ceramics - Watcharapasorn A. (2014)
Bismuth titanate and lanthanum-doped bismuth titanate ceramics were prepared from freeze-dried powders employing conventional solid state reaction and sintering procedures. The sintering process was carried out at 1150 °C from 4 up to 48 h. X-ray diffraction analysis showed that preferred orientation was reduced in bismuth titanate ceramic as sintering time increased while lanthanum-doped sample showed much less degree of preferred orientation and was independent of sintering time. Grain growth studies also showed that initial anisotropic grain growth rate was the main factor controlling the grain morphology, rendering the plate-shaped grain in both pure and lanthanum-doped bismuth titanate ceramics. Based on established grain growth law, pore-controlled diffusion could be the major mechanism determining the observed microstructure in these layered compounds. © 2009 Elsevier Ltd. All rights reserved.